Global scope of hospital pharmacy practice: a scoping review - Ahmed Abousheishaa, Aya; Sulaiman, Ahmad Hatim; Zaman Huri, Hasniza; Zaini, Syahrir; Othman, Nurul Adha; Aladdin, Zulhilmi; Ng, Chong Guan (MDPI, 2020)
The pharmacy profession has undergone tremendous changes over the past few decades. Pharmacists’ roles have expanded their boundaries to encompass more patient-centered services. However, the degree to which these roles are practised may vary. This scoping review is aimed at describing the extent and range of the professional pharmacy services offered in hospital pharmacies across different countries and the barriers underlying inappropriate or incomplete implementation of these services. Studies published in the English language between 2015 and 2019 were retrieved from the following databases: PubMed, CINAHL, Scopus, EBSCO Discovery Service, and Web of Science. A thematic analysis across the included studies produced two main themes. “Scope of practice” comprised three subthemes: pharmaceutical care practice, clinical pharmacy practice, and public health services and “Multiple levels of influence” comprised five subthemes: individual, interpersonal, institutional, community, and public policy-related factors. The hospital pharmacy services across countries ranged from traditional drug-centered pharmacy practice to a more progressive, clinically oriented practice. In some countries, there is an apparent inadequacy in the clinical pharmacy services provided compared to other clinical settings. Understanding the current pharmacy practice culture across different health care systems is an essential step towards improving the profession